Treatment of c-MET Antibody-Drug Conjugate Asymptomatic Pneumonitis with a Novel Steroid Regimen in Non–Small Cell Lung Cancer: A Case Report - Daniel A. Fox; Christine Tran; Vincent Blot; David S. Hong (Journal of Immunotherapy and Precision Oncology)
Antibody-drug conjugates (ADCs) are a potent class of antineoplastic drugs that deliver cytotoxic agents via targeting with monoclonal antibodies; however, ADCs are associated with high rates of lung toxicities, limiting the therapeutic potential in many patients. We report a case of a patient with metastatic non–small cell lung cancer taking the ADC telisotuzumab vedotin (Teliso V) plus osimtertinib who developed ADC-induced pneumonitis despite clinical benefit. This patient was able to tolerate treatment for a prolonged period on a novel steroid regimen, using steroids when pneumonitis was asymptomatic but radiologically evident and as a daily suppressant. This treatment strategy may have implications in the broader management of ADC–interstitial lung disease/pneumonitis and underscores its potential mechanisms.